Development of dog immune system - Pereira, Maria A (2021)
Immune system recognize and fight back foreign microorganisms and inner modifications that lead to deficient cell and tissue functions. During a dog's life, the immune system needs to adapt to different physiological conditions, assuring surveillance and protection in a careful and controlled way. Pregnancy alters normal homeostasis, requiring a balance between immunity and tolerance. The embryos and fetus should be protected from infections, while the female dog must tolerate the growing of semi-allografts in her uterus. After birth, newborn puppies are at great risk of developing infectious diseases, because their immune system is in development and immune memory is absent. Passive transfer of immunity through colostrum is fundamental for puppy survival in the first weeks of life, but hampers the development of an active immune response to vaccination. At the end of life, dogs experience a decline in the structure and functional competence of the immune system, compromising the immune responses to novel antigenic challenges, such as infections and vaccines. Therefore, the current article reviews the general processes related to the development of the dog´s immune system, providing an overview of immune activity throughout the dog's life and its implications in canine health, and highlighting priority research goals.